2017
DOI: 10.1074/jbc.ra117.000122
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the MDM2 RING domain enhances p53 transcriptional activity in mice

Abstract: The MDM2 RING domain harbors E3 ubiquitin ligase activity critical for regulating the degradation of tumor suppressor p53, which controls many cellular pathways. The MDM2 RING domain also is required for an interaction with MDMX. Mice containing a substitution in the MDM2 RING domain, MDM2, disrupting MDM2 E3 function and the MDMX interaction, die during early embryogenesis that can be rescued by p53 deletion. To investigate whether MDM2, which retains p53 binding, has p53-suppressing activity, we generated ; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…Many studies have shown that MDM2 can enhance p53 activity [27,28]. Moreover, previous investigation has revealed that p53 is a key modulator of cellular stress responses, becoming activated in ischemic areas of the brain and contributing to neuronal apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that MDM2 can enhance p53 activity [27,28]. Moreover, previous investigation has revealed that p53 is a key modulator of cellular stress responses, becoming activated in ischemic areas of the brain and contributing to neuronal apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite less frequently, in a number of investigations, the Cys involved in zinc coordination have also been efficiently mutated into serine. Indeed, this type of point mutation that results on E3 ligase inactivation has served to uncover, among others, the role of MDM2, RNF8, and SIAH1 RING E3s in cell cycle regulation, DNA damage response and Wnt signalling, respectively (Ji et al, 2017;Tian et al, 2017;Tripathi and Smith, 2017). Additionally, although there are fewer examples, it has been demonstrated that mutating the His into Glu, Tyr or Arg is sufficient to inactivate the ligase activity of MKRN1, RNF2, and RNF43 E3s, respectively (Xia et al, 2014;Loregger et al, 2015;Lee et al, 2018b; Figure 3).…”
Section: Inactivating Ring-type E3s By Mutating the Zinc-coordinatingmentioning
confidence: 99%
“…Therefore, Sox4 inhibits the ubiquitination of p53. As Mdm2 is a vital protein in mediating podocyte mitotic catastrophe and modulating p53, 29 , 30 , 31 we then analyzed whether Sox4 stabilized p53 by inhibiting in Mdm2-mediated p53 ubiquitination. As shown in Figure 6 G, the p53 protein level was reduced when Mdm2 was cotransfected into podocytes, while its expression was increased with increasing amounts of the Myc-Sox4 plasmid, indicating that the interaction between Sox4 and p53 is pivotal for the inhibitory effect of Sox4 on Mdm2-mediated p53 degradation.…”
Section: Resultsmentioning
confidence: 99%